76.5k views
1 vote
Thank you so much for helping

Thank you so much for helping-example-1
User Tetyana
by
5.6k points

1 Answer

3 votes

35.

answer

x^2+y^2-8x+12=0

Step-by-step explanation

center of the centre is at(4,0)

pick another point on the circles circumference=(4,2)

using the two points;(4,0) and (4,2) calculate the radius of the circle.

radius=√[(x2-x1)^2+(y2-y1)^2]

radius=√[(4-4)^2+(2-0)^2]

radius = 2units

general equation of a circle is given by;

(x-h)^2+(y-k)^2=r^2

where (h,k) is center and r is radius:

(x-4)^2+(y-0)^2=2^2

expanding the equation

x(x-4)-4(x-4)+y(y-0)-0(y-0)=4

x^2-4x-4x+16+y^2-0-0+0=4

collecting like terms

x^2-8x+y^2+16-4=0

x^2+y^2-8x+12=0

36.

answer

x^2+y^2-16x-12y+64=0

Step-by-step explanation

center=(8,6)

point (g,f)= (8,12)

radius=√[(8-8)^2+(12-6)^2]

radius=6units

substitution into;

(x-h)^2+(y-k)^2=r^2

(x-8)^2+(y-6)^3=6^2

x(x-8)-8(x-8)+y(y-6)-6(y-6)=36

x^2-8x-8x+64+y^2-6y-6y+36=36

x^2-16x+y^2-12y+100=36

x^2+y^2-16x-12y+64=0

User Sgoettschkes
by
5.7k points